(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
In this paper, a two stage acid etching (TSAE) technique has been developed and investigated to cleanup hard deposits on internal surfaces of boiler water wall tubes (WWTs) for a natural circulation highpressure drum boiler(fossil) unit: TIME-206-COB (Russia) at Ghorasal Thermal Power Station(GTPS), Bangladesh. TSAE technique was carried out very carefully by using a mixed solution of ammonium hydrogen fluoride, hydrochloric acid in presence of inhibitor urotropine and cleaning agent OP- 10(Russia).To attained maximum cleaning efficiency at each end of the cleaning stage compressed air 6kgfcm-2 was passed through the boiler WWTs by bottom headers very carefully. The overall close observations on the (TSAE)) cleaning operation revealed that not less than 90% of impurities were removed. The cleaning mechanism and the passivation on cleaned surface of boiler WWTs by 2.0% NaNO3 in presence of 0.5% NH4OH (pH 10.5) at 55Â°C were found to be satisfactory. Close macrostructural examinations (by SEM) of the tube materials after the TSAE operations reveled there is no remarkable corrosion or micro creaks on boiler WWTs materials. Key words: Boiler, Deposit, Passivation, Boiler water wall tubes (WWTs), Acid etching. DOI = 10.3329/bjsir.v43i3.1148 Bangladesh J. Sci. Ind. Res. 43(3), 333-344, 2008